Resolving Kirkuk Lessons Learned from Settlements of Earlier Ethno-Territorial Conflicts - Hanauer, Larry (RAND Corporation, 2012)
Past efforts to resolve ethno-territorial conflicts in Brčko, Mostar, Northern Ireland, and Jerusalem provide insights that could facilitate a negotiated settlement regarding the disputed Iraqi city of Kirkuk. The case studies show that Arabs, Kurds, and Turkomen must emphasize governance over symbols of sovereignty, develop adaptable power-sharing mechanisms, marginalize spoilers, empower local leaders, and create multi-ethnic security forces.